1981
DOI: 10.1128/iai.31.3.1193-1202.1981
|View full text |Cite
|
Sign up to set email alerts
|

Role of antigen form in development of mucosal immunoglobin A response to Shigella flexneri Antigens

Abstract: One major stumbling block in the development of an effective means to immunize against shigellosis and other enteric diseases has been the lack of a means to assess sequential mucosal immune responses to different potential immunogens. In the present study, we compared the abilities of live invasive organisms, noninvasive organisms, and nonviable antigen preparations of shigella to elicit mucosal immune responses. Whereas previous studies have found that effective immunity was produced best by vaccination with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

1983
1983
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…In the present study, we make use of our wellcharacterized, chronically isolated, ileal loop model in rabbits to follow the kinetics of the local immune response to parenterally administered Shigella flexneri antigen (8,10,11). Our earlier studies with this model system have demonstrated that a vigorous secretory IgA memory response can be elicited in intestinal secretions by oral priming with live, locally…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, we make use of our wellcharacterized, chronically isolated, ileal loop model in rabbits to follow the kinetics of the local immune response to parenterally administered Shigella flexneri antigen (8,10,11). Our earlier studies with this model system have demonstrated that a vigorous secretory IgA memory response can be elicited in intestinal secretions by oral priming with live, locally…”
mentioning
confidence: 99%
“…invasive Shigella X16 (a hybrid of Escherichia coli and S. flexneri) (7)(8)(9)(10)(11)(12)(13). The present study demonstrates that local IgA response can be elicited to S. flexneri by parenterally administered, killed Shigella X16.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Originally employed in investigations of intestinal absorption [Parsons, 19671, Thiry-VelIa loops have recently been used in a number of studies of secretory IgA immune responses occurring in the bowel of rabbits , 1981, 1982. Few, however, have considered variables inherent in the loop model itself that might affect the results obtained.…”
Section: Discussionmentioning
confidence: 99%
“…The problem of the accessibility of tissues for inoculation and sampling was overcome by adapting the chronically isolated Thiry -Vella rabbit ileal loop model of Keren et al [ 19751. This model has been extensively employed in investigations of local IgA responses to various antigens including bacteria , 1981, 1982 and keyhole limpet hemocyanin [Hamilton et al, 19781. It was necessary to find a virus which would not normally infect this site, but which was capable of replicating and persisting locally in the isolated loops, in order to avoid the likelihood of experimental results being obscured by anamnestic responses. Paramyxoviruses, although normally respiratory pathogens, are known to be capable of replicating in small intestinal organ cultures [Rubenstein and Tyrreli, 19701 and have been shown to infect other nonrespiratory tissues, including lymphoid cells, neurones, and the endothelial cells of blood vessels and the urinary bladder [Russell and Edington, 19851.…”
Section: Introductionmentioning
confidence: 99%